2007
DOI: 10.1111/j.1525-1314.2007.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

A new thermodynamic model for clino‐ and orthoamphiboles in the system Na2O–CaO–FeO–MgO–Al2O3–SiO2–H2O–O

Abstract: A recent thermodynamic model for the Na-Ca clinoamphiboles in the system Na 2 O-CaO-FeO-MgOAl 2 O 3 -SiO 2 -H 2 O-O (NCFMASHO), is improved, and extended to include cummingtonite-grunerite and the orthoamphiboles, anthophyllite and gedrite. The clinoamphibole model in NCMASH is adopted, but the extension into the FeO-and Fe 2 O 3 -bearing systems is revised to provide thermodynamic consistency and better agreement with natural assemblage data. The new model involves order-disorder of Fe-Mg between the M2, M13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
307
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 464 publications
(315 citation statements)
references
References 57 publications
4
307
0
4
Order By: Relevance
“…4). Thermodynamic models of Ep and Chl are after Holland and Powell (1998), and that of amphibole after Diener et al (2007). Ab and Qz are considered as pure phases.…”
Section: Discussionmentioning
confidence: 99%
“…4). Thermodynamic models of Ep and Chl are after Holland and Powell (1998), and that of amphibole after Diener et al (2007). Ab and Qz are considered as pure phases.…”
Section: Discussionmentioning
confidence: 99%
“…6.6.8 (Connolly 2005(Connolly , 2009updated 2013) with the dataset of Powell (1998, updated 2002) and the CORK equation of state of fluids Powell 1991, 1998). Adopted solution models were Diener et al, (2007) for clinoamphibole, for olivine and spinel, Holland and Powell (1996) for orthopyroxene and clinopyroxene, for chlorite, and Holland and Powell (2003) for plagioclase.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous workers have demonstrated that is it an extremely powerful and useful method for providing detailed P-T-X information for a variety of metamorphic environments (e.g. Powell et al, 1998;Vance and Mahar, 1998;White et al, 2001;Cononolly and Petrini, 2002;White et al, 2003;Zeh et al, 2004;Harris et al, 2004;White et al, 2004;Evans, 2004;Johnson and Brown, 2004;Pelletier et al, 2005;White et al, 2005;Kelsey et al, 2005;Stipska and Powell, 2005;Zeh et al 2005a,b;Konrad-Schmolke et al, 2006;Tenczer et al, 2006;Dziggel et al, 2006;White et al, 2007;Diener et al, 2007;Powell and Holland, 2008;White et al, 2008;Millonig et al, 2008;Diener et al, 2008;Kelsey et al, 2008;Mahan et al, 2008). A recent paper by Powell and Holland (2008) discusses at the length the advantages and disadvantages of a pseudosection approach in comparison to a conventional thermobarometric approach.…”
Section: Pseudosection Thermobarometry Versus Conventional Thermobaromentioning
confidence: 99%